1994
DOI: 10.1111/j.1532-5415.1994.tb04979.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Acute Care Geriatric Inpatient Units Under the Present Medicare Prospective Payment System

Abstract: The Mount Sinai Medical Center's Geriatric Evaluation and Treatment Unit (GETU) is a 16-bed acute care geriatric unit that operates under the Medicare Prospective Payment System (PPS) in an academic medical center environment. The Medicare PPS and the needs of our local health care system have played a considerable role in the development and operation of our inpatient acute care geriatric unit. The GETU provides acute geriatric care and geriatric assessment and is a site for education and clinical research. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several authors have recently reported positive patient outcomes and shorter lengths of stay on specialized acute geriatric units (Pawlson, 1988;Applegate, Miller, Graney, Elam, Burns & Akins, 1990;Inouye, Acampora, Miller, Fulrner, Hurst & Cooney, 1993;Stuck, Siu, Wieland, Adam & Rubenstein, 1993;Fillit & Miller, 1993;Miller, Applegate, Elam & Graney, 1994;Fillit, 1994).…”
Section: Review Of the Literalurementioning
confidence: 99%
“…Several authors have recently reported positive patient outcomes and shorter lengths of stay on specialized acute geriatric units (Pawlson, 1988;Applegate, Miller, Graney, Elam, Burns & Akins, 1990;Inouye, Acampora, Miller, Fulrner, Hurst & Cooney, 1993;Stuck, Siu, Wieland, Adam & Rubenstein, 1993;Fillit & Miller, 1993;Miller, Applegate, Elam & Graney, 1994;Fillit, 1994).…”
Section: Review Of the Literalurementioning
confidence: 99%
“…With trends in managed care reimbursement, more psychologists are able to turn to work in nursing homes as another viable source of income (Hartman-Stein, 1997). Changes in Medicare, such as the Prospective Payment System and the influence of managed care (see Fillit, 1994; Wells et al, 1993), are beyond the scope of this article, but we mention them because they are likely to soon affect the reimbursement of psychologists and thus the ability of psychology to contribute in the nursing home setting. These potential changes aside, Medicare work remains to date a workable option for psychologists interested in working with elderly clients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the educational impact of an acute care geriatric unit with respect to medical student, resident, and fellow physician education have been described previously in other programs, none have described this educational process in a community hospital setting 6 . The educational benefits to nurses are reflected by the yearly educational needs assessment showing increasing knowledge in geriatric nursing as reflected by the increased completion rate of the geriatric unit's Geriatric Nursing Assessment Program and Geriatric Nursing Competencies from 1992 to 1995 and certification in gerontology.…”
Section: Discussionmentioning
confidence: 99%
“…The program's main purpose was to facilitate and enhance the quality of care rendered to older hospitalized patients. Objectives included: (1) education of resident, faculty, and staff physicians, nurses, and paraprofessionals regarding up‐to‐date principles of geriatric care; (2) maximizing patient functional independence; (3) maximizing patient nutritional status; (4) minimizing patient medication and reducing polypharmacy; (4) focusing on appropriate patient skin care; and (6) addressing ethical issues.…”
mentioning
confidence: 99%